Organizational Commitments That Shape Turnover Intention, Employee Performance, And Organizational Citizenship Behavior - Masagus Safei; Unggul Kustiawan (ijd-demos, 2022)
Abstract:The research objectives are to explore the effect of perceived organizational support (POS), job satisfaction (JS), and employee engagement (EE), which form organizational commitment (OC). Thus, increase influencing Turnover Intention (TI), Employee Performance (EP), and Organizational Citizenship Behavior (OCB). In addition, it is also about the effect of POS on JS and the influence of OCB on EP. Finally, it is the development of several previous studies. The survey used a purposive sampling method on 203 State Civil Apparatus (ASN) employees of community Health centers (Puskesmas) in Tangerang Regency, Banten Province, Indonesia. For analysis using factor analysis and structural equation modeling (SEM) Lisrel. The findings of this study are organizational support, employee satisfaction, and involvement increase organizational commitment so that it positively affects Turnover Intention, Employee Performance, Organizational Citizenship Behavior. In addition, organizational support increases employee satisfaction. Likewise, Organizational Citizenship Behavior has a positive effect on Employee Performance.Keywords: perceived organizational support, organizational commitment, organizational citizenship behavior. Abstrak:Tujuan penelitian adalah untuk mengeksplorasi pengaruh dari persepsi dukungan organisasi (POS), kepuasan kerja (JS), dan keterlibatan karyawan (EE), yang membentuk komitmen organisasi (OC). Dengan demikian, peningkatan mempengaruhi Turnover Intention (TI), Employee Performance (EP), dan Organizational Citizenship Behavior (OCB). Selain itu juga tentang pengaruh POS terhadap JS dan pengaruh OCB terhadap EP. Terakhir, merupakan pengembangan dari beberapa penelitian sebelumnya. Survei menggunakan metode purposive sampling pada 203 pegawai Aparatur Sipil Negara (ASN) Pusat Kesehatan Masyarakat (Puskesmas) di Kabupaten Tangerang, Provinsi Banten, Indonesia. Untuk analisis menggunakan analisis faktor dan structural equation modeling (SEM) Lisrel. Temuan penelitian ini adalah dukungan organisasi, kepuasan karyawan, dan keterlibatan meningkatkan komitmen organisasi sehingga berpengaruh positif terhadap Turnover Intention, Kinerja Karyawan, Organizational Citizenship Behavior. Selain itu, dukungan organisasi meningkatkan kepuasan karyawan. Demikian juga Organizational Citizenship Behavior berpengaruh positif terhadap Kinerja Karyawan.Katakunci:dukungan organisasi, komitmen organisasi, perilaku kewarganegaraan dalam berorganisasi.